Relationship between destination attractiveness and decision to visit Kuala Selangor, Malaysia - Mohamed Zakaria, Hasan (2018)
Attractiveness is widely accepted as a great influence in a visitor’s destination of choice, desire of fulfilment, intention to revisit, perception of benefits and motivations, positive impression of sentiment pioneers, the measure of cash spent, and duration of stay. Therefore, this study aims to provide a deeper knowledge on visitors’ perceived attractiveness of a destination. The mediating role of the perceived importance of an attractiveness attribute and the ability of the destination to fulfil visitors’ need was assessed. This present study attempts to examine the satisfaction of visitors from the importance and ability of the attractiveness attributes. From the importance and ability assigned by the visitor, an IPA analysis was conducted. A survey has been conducted between May to June 2017 at multiple attraction sites in Kuala Selangor. A total of 390 responses were analysed using IBM SPSS 23 software program. Multi Attribute Model was used by specifying the attractiveness attribute to measure the overall destination attractiveness. The result shows that heritage, history, and cultural attraction attractiveness attribute were perceived as the most important (M= 4.05) and having the highest ability to satisfy the needs of the visitors (M = 4.28). The results obtained also showed that the same attractiveness attribute had the highest attractiveness score (M =17.33), and that it was the only attractiveness attributes that satisfied visitors. The current study also found that Kuala Selangor has low attractiveness as the score is 10.89 out of 25.00. In conclusion, these findings will provide additional knowledge on how domestic visitors perceive the attractions in Kuala Selangor and on which attribute to be focused by destination marketers for future marketing strategy.